Rancang Bangun ALPENLIBE (Alat Pemanen Energi Listrik Berbasis Piezoelektrik) Sebagai Upaya Mewujudkan Energi Terbarukan - Listijorini, Erny; Susilo, Sidik; Adhiwindoro, Akhmad; Febrianto, Ilham; Shihab, Muhammad Alwi; Dwiyoga, Muhammad Ashari; Ananda, Rafi Rizqi (Rekayasa Material, Manufaktur dan Energi, 2024)
Utilizing alternative energy as an effort to use energy needs to be done. One is energy harvesting, which is capturing minute amounts of energy from one or more surrounding energy sources, collecting and storing them for later use. There are examples of uses in harvesting energy from vibrations, which are carried out using piezoelectricity as a converter into electrical energy. A piezoelectric-based electrical energy harvesting device has been designed using a cantilever method from mechanical pressure from humans climbing stairs. This research uses an experimental method where there are variations in the load given by humans of 55 Kg, 65 Kg, and 75 Kg to provide a force on an energy harvester that has four piezoelectric circuits installed, which are installed in series and parallel totaling 38 piezoelectric units. , where the four circuits have a number of piezoelectrics of 10, 8, 10, and 8 piezoelectrics on each side. The resulting voltage will later be rectified using a rectifier bridge until it is temporarily stored in the capacitor. As obtained from the calculation results, the voltage values for each load are 7.762 mV, 11.103 mV, and 17.55 mV, respectively.